2014
DOI: 10.1002/pi.4781
|View full text |Cite
|
Sign up to set email alerts
|

Biopolymer nanocomposites based on poly(hydroxybutyrate-co -hydroxyvalerate) reinforced by a non-ionic organoclay

Abstract: In this study, a nanocomposite based on a biodegradable polymer poly(hydroxybutyrate-co-hydroxyvalerate) (PHBV) reinforced by triethylene glycol mono-n-decyl ether (C 10 E 3 ) non-ionic organoclay (C 10 E 3 -Mt) was prepared. The morphology and the thermal and mechanical properties of PHBV/C 10 E 3 -Mt were compared with those of PHBV nanocomposites prepared using commercial organically modified montmorillonite Cloisite ® 30B (OMt) and raw montmorillonite (Mt). Nanocomposites with 3 wt% nanoparticles were obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…Research interest has recently shifted towards the use of other organo-modifiers, including non-traditional cationic salts e.g. quarternary phosphonium salts (Ollier et al, 2013), and nonionic surfactants (Carli et al, 2015), among others.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…Research interest has recently shifted towards the use of other organo-modifiers, including non-traditional cationic salts e.g. quarternary phosphonium salts (Ollier et al, 2013), and nonionic surfactants (Carli et al, 2015), among others.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…The introduction of reinforcing nanoparticles into a continuous polymer phase to form eco-friendly green nanocomposites has attracted a great deal of attention [235][236][237]. The use of chitin nanowhiskers (ChW) as a reinforcing nanofiller in the polymer matrix provides positive environmental benefits with respect to ultimate disposability and raw material use as well as strong mechanical properties.…”
Section: Biopu-based Nanocompositesmentioning
confidence: 99%
“…The resulting hybrid layered material exhibits a change of its chemical nature that switches from hydrophilic to hydrophobic. These modifications allow the adsorption of neutral organic compounds and offer numerous applications 1,[7][8][9] . The first is relied to environmental issue, where many authors suggested the use of organoclays as geochemical layers for the capture of hydrophobic pollutants which usually pass through the natural clay barrier implemented against pollution, or as sorbent materials for water remediation.…”
Section: Introductionmentioning
confidence: 99%
“…Smectite clay minerals such as Wyoming montmorillonite display, in presence of water, cation exchange capacities (CEC), swelling, hydration properties and a high surface area which lead to strong adsorption properties. These properties have been highlighted in several applications involving catalysis, nanocomposite materials, geochemical barriers in the case of waste landfills as well as potential sorbents for water remediation [1][2][3][4][5][6][7][8] . The structure of dioctahedral smectite is represented by two Si 4 O 10 tetrahedral sheets of sandwiching an aluminum (Al 4 (OH) 12 ) or a magnesium (Mg 6 (OH) 12 ) octahedral sheet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation